2022
DOI: 10.4236/jacen.2022.114020
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Pesticide Residues in Soils of Cotton Farming Areas in Togo

Abstract: The main cash crop in Togo is cotton, with about 70% of agricultural exports. This crop is very dependent on the use of chemical inputs, in particular pesticides. Pesticides used in cotton farming in Togo include organochlorines, triazines, organophosphates and pyrethroids. We conducted a study on the impact of these pesticide use, in particular organochlorines and triazines, on cotton farming soils. We chose the Plateaux region (southern Togo) as the study area because of its high cotton production. Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…The survey also revealed that the majority of growers use chemical fertilizers, but only 12% of them know how to apply and use them. This lack of knowledge of fertilizer dosages could affect the sustainability of vegetablegrowing systems and pose a risk to the environment [6]. In fact, the work of [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey also revealed that the majority of growers use chemical fertilizers, but only 12% of them know how to apply and use them. This lack of knowledge of fertilizer dosages could affect the sustainability of vegetablegrowing systems and pose a risk to the environment [6]. In fact, the work of [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, mismanagement of these products can entail health and environmental risks [5]. Excessive use of compound or nitrogen fertilizers is a source of nitrates that contaminate surface and underground water [6]. In addition, the pressure of pests (parasites and harmful insects) is a major constraint on the vegetable-growing sector, and contributes to the decline in production and producers' incomes.…”
Section: Introductionmentioning
confidence: 99%
“…It is also heavily dependent on pesticides. Pyrethroids (PYR), organophosphorus (OP), triazine and carbamate pesticides are the most widely used families throughout the country [6,7]. Although these groups of pesticides are considered easily biodegradable, some are extremely toxic, especially to aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%